Trade and economic cooperation between Ukraine and the EU at the current stage - Mishchuk, Yuliia Viktorivna (Волинський національний університет імені Лесі Українки, 2025)
The relevance of the research topic is determined by the fact that trade and economic cooperation between Ukraine and the EU is becoming particularly important in the context of Russian aggression and Ukraine's aspirations for European integration, which requires a comprehensive analysis of the current state of relations and prospects for their development. This bachelor's work examines the theoretical and methodological foundations of trade and economic cooperation between Ukraine and the EU. The first chapter of the bachelor's work summarises the theoretical and methodological foundations of trade and economic cooperation between Ukraine and the EU. The main principles of economic integration are systematized and the evolution of the legal framework of cooperation from the Partnership Agreement to the Association Agreement is examined. The second chapter of the bachelor's work analyses the current state of trade and economic relations between Ukraine and the EU. The dynamics and structure of bilateral trade, investment cooperation, and the impact of war on economic relations are studied. The third chapter of the bachelor's work reveals the main problems and prospects for the development of trade and economic cooperation between Ukraine and the EU. Key barriers in relations are identified and prospects for deepening integration in the context of obtaining EU candidate status are outlined.
Keywords: Ukraine; EU; trade and economic cooperation; European integration; Association Agreement; free trade area; bilateral trade; investment cooperation; economic relations